Depresión y ansiedad en gestantes con aborto diferido. Hospital Provincial General Docente Riobamba, 2020 - Santiago Ruperto, Hidalgo Pulia (2021)
ABSTRACT This study focused on determining the presence of depression and anxious feelings in patients with a diagnosis for deferred abortion who were treated at “Provincial General Docente Riobamba hospital” in the period (January - December 2020), for this purpose the following methods were used: collection of data from the medical records provided by the hospital's statistics department and the application of the Beck test plus an additional question that will allow the chosen sample to identify anxiety through the emotional factor. This study revealed that among the 30 patients, 33% had mild depression, 7% a state of moderate depression, while the other 60% had minimal or no depression. The patients also exhibited various symptoms such as decreased appetite, sleep deprivation, and daily activity. In addition, it is important to mention that 40% of the patients reflect anxiety, since they report that they do not want to get pregnant again, thus qualifying the 60% who want a future pregnancy, the same group that has minimal or no depression. Keywords: depression, anxiety, abortion, delayed abortion, Beck's test. Reviewed by: Lic. Dario Javier Cutiopala Leon ENGLISH PROFESSOR c.c. 060458106